The European Status Quo in legal recognition and patient‐care services of occupational skin cancer. (April 2016) - Ulrich, C.; Salavastru, C.; Agner, T.; Bauer, A.; Brans, R.; Crepy, M.N.; Ettler, K.; Gobba, F.; Goncalo, M.; Imko‐Walczuk, B.; Lear, J.; Macan, J.; et al.
Abstract: Background: Skin cancer is the most common malignancy in Caucasian populations worldwide and ultraviolet radiation (UVR) is known for being the number one carcinogen. As, especially in outdoor workers, UVR is an inevitable carcinogen, the prevention and management of UVR‐related skin cancers in these at‐risk populations represent a collective challenge for dermatologists and healthcare policymakers likewise. Objective: To provide an overview on the current regulations on the acknowledgement and management of work‐related skin cancer in 11 European countries. Methods: Dermatologists from 11 countries networking within the EU Horizon 2020 COST Action TD1206 'StanDerm' contributed to a standardized survey regarding current national regulations, implemented for the recognition, prevention and management as well as possible compensation regulations in their individual country of residence. Results: Ten of 11 participating countries in this survey reported the existence of an established programme available on certain occupational diseases; work‐related skin diseases were only specifically recognized in eight countries. Seven of 11 countries recognize cutaneous squamous cell carcinoma in outdoor workers as 'occupational skin cancer'. Basal cell carcinoma (6 of 11), actinic keratosis (5 of 11), Bowen's disease (5 of 11) and malignant melanoma (5 of 11) are not as regularly approved as potentially 'work‐induced'. Only a few of the countries included into this survey established a general documentation system (national registry) on occupational skin diseases. So far, representatives of only three countries of this survey referred to a specific established national programme for the prevention, management or compensation of occupational skin cancers acquired during work‐related UVR exposure. Conclusion: This survey highlights the need for mandatory regulations on the prevention, management and potential compensation of work‐related UV‐induced skin cancer across Europe. Against the background of a joint European domestic market, equal standards of occupational safety across Europe should include binding regulations for the protection and management of work‐related skin cancer. The design of a common regulation to meet the increasing incidence of skin cancers in outdoor workers should become part of the European agenda, ensuring equal working and living conditions in the member states.